Transformasi Timbre dalam Gamelan Bali: Eksplorasi Resonator Digital pada Gender Wayang - Sukawiadnyana, I Gede Yogi (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study discusses the modification of Balinese gender wayang instruments by replacing physical resonators with digital resonators based on the Digital Audio Workstation (DAW) Ableton Live software. It focuses on the practice carried out by Barga Sastrawadi, a musician and composer in the experimental music group Kadapat. A qualitative approach is used to explore the creative process, technical aspects, and artistic considerations in the modification. Research methods: Data were collected through in-depth interviews, Ableton Live patch observations, and a study of the potential and limitations of digital resonators. Results and discussion: This study shows that digital resonators can be an effective alternative to overcome the mobility limitations of gender wayang instruments without completely eliminating their distinctive sound quality. The use of this technology also presents challenges such as changes in the physical interaction of players and high technical demands. Implication: Digitalization of gamelan is not only a technical solution, but also a form of cultural adaptation that opens up new possibilities in contemporary music practice.